Навершя із Чмиревої Могили (знахідка 1898 року - Бабенко, Л.І. (Археологія і давня історія України, 2019)
Статтю присвячено публікації та аналізу скіфських навершь, прикрашених фігуркою бородатого оленя, виораних селянами у 1898 р. поблизу Чмиревої Могили, що нині зберігаються у колекціях Державного Ермітажу та Харківського історичного музею імені М. Ф. Сумцова. In 1898 during excavations of Chmyreva Mohyla held by F. Brown, near the burial mound the countrymen plowed four bronze finials in shape of bearded deer. The finials were taken to the Hermitage collection, and in 1932 they were given to Ukraine, to Kharkiv, and now they are in the collection of the M. F. Sumtsov Kharkiv Historical Museum. On the outside the finials from Chmyreva Mohyla are close to those from the Haimanova Mohyla. But they are different in that they are less schematic, more variable inside the series and that they have more clear relief of the small details.